Plastic Bodies : Sex Hormones and Menstrual Suppression in Brazil - Sanabria, Emilia, 1979- (Book collections on Project MUSE., 2016)
In Plastic Bodies Emilia Sanabria examines how women's use of sex hormones in Bahia, Brazil for menstrual suppression shapes social relations, having become central to contemporary understandings of the body, class, gender, sex, personhood, modernity, and Brazilian national identity.